IDENTIFICATION OF THE MORPHOLOGICAL CHARACTERS INFLUENCING THE INFES- TATION RATE OF YELLOW STEM BORER - Shahjahan, M; Hossain, M (Biological Sciences - PJSIR, 2003)
Resistnce of twenty one aus and eleven aman varieties of rice to yellow stem borer (YSB) infestation in relation to their morphological characters were determined. Different morphological characters varied significantly among test varieties. In aus season stem diameter, leaf number, flag leaf length and width, 2nd leaf length and width and life duration of rice plant induced YSB infestation but greater plant height, increased tiller number and leaf macro hairs reduced the infestation rate. The combined influence of these ten independent variables on YSB infestation was 64 percent. In aman season the correlation values indicated that wider stem, increased tiller number, greater flag leaf length and width and wider 2nd leaf induced higher infestation. On the other hand, longer plant, more leaf number, the greater 2nd leaf length, more leaf hairs and increased life duration of plant decreased YSB infestation rate. The combined influ- ence of these seven independent variables on YSB infestation was 85 percent. These findings are indicative of the exis- tence of potential sources of resistance in different rice varieties. Incorporation of such resistance factors in commercial rice varieties will be of immense importance in preventing losses by YSB and in reducing YSB population cumulatively.